2018
DOI: 10.4236/ce.2018.95050
|View full text |Cite
|
Sign up to set email alerts
|

Dental Apps for Smartphones: New Way of Providing Services and Education

Abstract: Objective: To review the literature about dental applications (DAPP) for smartphones (SP) and search/describe DAPP available in Portuguese, in 3 operating systems. Methods: Aiming the review, the terms "smartphones", "app" and "dentistry" were searched in the databases Pubmed, Virtual Health Library (BVS) and Google Scholar. Based on the review results, DAPP were searched for teaching and learning (TL), clinical practice (CP), patient orientation (PO) and professional update (PU), in Portuguese, in the Android… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
7
0
3
Order By: Relevance
“…A study conducted in Brazil reported that most mobile phone apps had not been certified by any dental organization. They recommended that such apps should provide the most recent evidence-based information and should be periodically monitored in terms of quality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Brazil reported that most mobile phone apps had not been certified by any dental organization. They recommended that such apps should provide the most recent evidence-based information and should be periodically monitored in terms of quality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Las Apps de salud oral constituyen un medio importante para acceder a cuidados e información de salud oral, creando un nuevo ambiente de aprendizaje para disminuir inequidades en salud y entregar información para la promoción de la salud oral. (15) El conocimiento es indispensable para generar cambios de conducta y actitud, pero no se asegura el éxito con la sola entrega de información. (9,10) Está comprobado que creer en la habilidad de realizar una actividad por sí mismo predice cómo resulta, lo que es importante para el comportamiento en salud oral.…”
Section: Discussionunclassified
“…(11) Los avances tecnológicos en smartphones y Apps han influenciado el acceso a la información y métodos de comunicación paciente-profesional en salud. (15) La versatilidad de los smartphones permite la entrega de información visual, textual y con videos, además de permitir personalizar la información para enviar recordatorios y monitorizar el progreso individual. (4,17) El uso de Apps, mensajes de texto e internet han demostrado que permiten influenciar comportamientos de salud en la población para controlar enfermedades crónicas, (2,12,13) mejorando el control de factores de riesgo, la adherencia a tratamientos, (18) y compromiso de los pacientes.…”
Section: Uso De Tecnología Para La Promoción De La Saludunclassified
See 1 more Smart Citation
“…. Faria et al (21) reviewed 215 smartphone dental applications, 38 (17.67%) of them for Teaching and learning purposes. Regarding the teaching and learning process, the authors highlighted the importance of using smartphone applications as a new tool available to facilitate learning.…”
Section: Effect Of Using the Smartphone Dental Applicationmentioning
confidence: 99%